Novel Paramyxoviruses in Bats from Sub-Saharan Africa, 2007–2012 - Mortlock, Marinda; Kuzmin, Ivan V.; Weyer, Jacqueline; Gilbert, Amy T.; Agwanda, Bernard; Rupprecht, Charles E.; Nel, Louis H.; Kearney, Teresa; Malekani, Jean M.; Markotter, Wanda (Emerging infectious diseases, 2015)
As part of a larger survey for detection of pathogens among wildlife in sub-Saharan Africa conducted during 2007-2012, multiple diverse paramyxovirus sequences were detected in renal tissues of bats. Phylogenetic analysis supports the presence of at least 2 major viral lineages and suggests that paramyxoviruses are strongly associated with several bat genera.